Translucent Y-α-SiAlON ceramics with enhanced mechanical properties prepared from sub-micrometre-sized powders. Issue 18 (15th December 2020) - Zhu, Jiatong; Xu, Jie; Lv, Shun; Cao, Shuyao; Luo, Jie; Meng, Xuanyu; Gao, Feng
Abstract: Y-α-SiAlON powders with different compositions were calcined by a high-temperature, solid-phase method. The effect of calcination temperature and dwelling time on the phase and microstructure of the powders was investigated. Powders with a composition of Y0.4 Si9.3 Al2.7 O1.5 N14.5 (m = 1.2, n = 1.5) were obtained through calcining at 1600 °C for 5 h. Y-α-SiAlON ceramics were prepared by hot pressing using the as-prepared sub-micrometre-sized Y-α-SiAlON powders. XRD and TEM results indicate that Y-α-SiAlON ceramics possess a highly purity phase. Nano-sized Y2 O3 and Yb2 O3 sintering aids were added to densify the Y-α-SiAlON ceramics, resulting in enhanced mechanical properties and optical transmittance. Y-α-SiAlON ceramics with Yb2 O3 showed better mechanical properties than those with the addition of Y2 O3 . With the addition of Yb2 O3, Y-α-SiAlON ceramics showed a hardness, bending strength and reduced modulus of 32.90 ± 3.34 GPa, 577.84 ± 18.37 MPa and 284.39 GPa, respectively. However, the long columnar grains and glass phase in Y-α-SiAlON ceramics with the addition of Yb2 O3 resulted in a lower transmittance. Y-α-SiAlON ceramics with the addition of Y2 O3 exhibited an optical transmittance of 32% in the mid-infrared region.